Management of opioid use disorder, opioid withdrawal, and opioid overdose prevention in hospitalized adults: A systematic review of existing guidelines. Issue 9 (26th July 2022) - Calcaterra, Susan L.; Bottner, Richard; Martin, Marlene; Englander, Honora; Weinstein, Zoe M.; Weimer, Melissa B.; Lambert, Eugene; Ronan, Matthew V.; Huerta, Sergio; Zaman, Tauheed; Ullal, Monish; Peterkin, Alyssa F.; et al.
Abstract: Background: Hospitalizations related to the consequences of opioid use are rising. National guidelines directing in‐hospital opioid use disorder (OUD) management do not exist. OUD treatment guidelines intended for other treatment settings could inform in‐hospital OUD management. Objective: Evaluate the quality and content of existing guidelines for OUD treatment and management. Data Sources: OVID MEDLINE, PubMed, Ovid PsychINFO, EBSCOhost CINHAL, ERCI Guidelines Trust, websites of relevant societies and advocacy organizations, and selected international search engines. Study Selection: Guidelines published between January 2010 to June 2020 addressing OUD treatment, opioid withdrawal management, opioid overdose prevention, and care transitions among adults. Data Extraction: We assessed quality using the Appraisal of Guidelines for Research and Evaluation (AGREE) II instrument. Data Synthesis: Nineteen guidelines met the selection criteria. Most recommendations were based on observational studies or expert consensus. Guidelines recommended the use of nonstigmatizing language among patients with OUD; to assess patients with unhealthy opioid use for OUD using the Diagnostic Statistical Manual of Diseases —5th Edition criteria; use of methadone or buprenorphine to treat OUD and opioid withdrawal; use of multimodal, nonopioid therapy, and when needed, short‐acting opioid analgesics in addition to buprenorphine or methadone, for acute pain management; ensuring linkage to ongoing methadone or buprenorphine treatment; referring patients to psychosocial treatment; and ensuring access to naloxone for opioid overdose reversal. Conclusions: Included guidelines were informed by studies with various levels of rigor and quality. Future research should systematically study buprenorphine and methadone initiation and titration among people using fentanyl and people with pain, especially during hospitalization.